It’s In Our Hands: facilitating agency, personal connections and collective cohesion in climate education through board game play - Annie Padwick; Emma P. Hocking; Joe Shimwell; Carol Davenport; Julia Bourne; Kayleigh Ransome; Chelsea Baxter; Alan Ramsay; Edward Blazey (Journal of Environmental Studies and Sciences, 2026)
The complexity of climate change can make it difficult for younger children to engage with it. We present the co-design and piloting of a serious game about climate change, designed for civic as well as educational purposes. An existing game developed by the authors was revised through co-design with children, teachers and outreach practitioners, facilitated by a participatory design agency. Co-design identified nine key areas of improvement of the game: title; geographic location; language; teacher resources; classroom pedagogy; scoring; board; accompanying cards; and scalability. The language and design of the final version was revised to ensure it was accessible to children and could be facilitated by teachers in a classroom setting. Piloting was undertaken with a further 73 primary school children in two schools in Northeast England to assess whether gameplay in classrooms could generate the desired intrapersonal and learning outcomes. Ethnographic analysis of data indicates the game can help children to develop their agency in climate-decision making, foster real-world connections with climate change, and realise the collective cohesion and urgency needed to tackle climate change, as well as develop understanding of the climate change system. Other more emergent themes included the parallels between game discussions and real-world decision making on climate change, including the important role of strong leaders and advocates, and the level of responsibility and ownership children took in the game.

Millennial-scale fire and climate dynamics in the world's largest tropical wetland show emerging fire threat to flooded ecosystems - Bronwen S. Whitney; Danilo M. Neves; Nicholas J.D. Loughlin; Carlos D'Apolito; Carla Coblinski Tavares; Emma P. Hocking; Francis E. Mayle; Mitchell J. Power; Aguinaldo Silva; Mario L. Assine (Global and Planetary Change, 2026)

Environmental response of coastal lake Huelde, Chile, after tsunami inundation and earthquake-induced subsidence - Emma P. Hocking; Philipp Kempf; Krzysztof Pleskot; Magdalena Suchora; Piotr Kołaczek; Markus Niederstätter; Jasper Moernaut (Quaternary Science Reviews, 2025)

Global vegetation zonation and terrestrial climate of the warm Early Eocene - Nick Thompson; Ulrich Salzmann; David K. Hutchinson; Stephanie L. Strother; Matthew J. Pound; Torsten Utescher; Julia Brugger; Thomas Hickler; Emma P. Hocking; Daniel J. Lunt (Earth-Science Reviews, 2025)

Biostratigraphy and Paleoenvironments of the Pirabas Formation (Neogene, Pará State-Brazil) - Bianca Tacoronte Gomes; Orangel Aguilera; Silane Aparecida Ferreira da Silva-Caminha; Carlos D'Apolito; Damián Cárdenas; Emma P. Hocking; Karyen Ketly Batista Lemes (Marine Micropaleontology, 2023)

The late Holocene introduction of Juglans regia (walnut) to Cyprus - Matthew J. Pound; Calian J. Hazell; Emma P. Hocking (Vegetation History and Archaeobotany, 2023)
The island of Cyprus has a long history of human impacts, including the introduction of more than 250 plant species. One of these introduced species is Juglans regia (walnut), which is considered a naturalised non-native (introduced in last 500 years). Here we report the earliest occurrence of Juglans regia pollen grains from a sedimentary deposit on Cyprus. The pollen recovered from the Akrotiri Marsh provides an earliest introduction date of 3,100-3,000 cal yr bp . This Bronze Age occurrence of Juglans regia is sporadic. However, by 2,000 cal yr bp the pollen signal becomes more persistent and indicates that introduction or expansion of Juglans regia was highly likely in the Roman period. We integrate our new results with younger pollen occurrences of Juglans regia on Cyprus, the archaeobotanical record and documentary evidence to provide an overview of this archaeophyte. Our findings show that, following the conventions of the Flora of Cyprus, Juglans regia should be reclassified from naturalised non-native to indigenous.

High-resolution Bronze Age palaeoenvironmental change in the Eastern Mediterranean: exploring the links between climate and societies - Calian J. Hazell; Matthew J. Pound; Emma P. Hocking (Palynology, 2022)

Modern diatom assemblages from Chilean tidal marshes and their application for quantifying deformation during past great earthquakes - Emma P. Hocking; Ed Garrett; Marco Cisternas (Journal of Quaternary Science, 2017)
Tidal marsh sediments from south‐central Chile provide evidence for multiple great earthquakes. Diatom transfer functions, statistical models of the relationship between species preserved in the sediment and elevation, provide quantitative estimates of coseismic vertical land‐level change associated with individual earthquakes. However, in south‐central Chile, our ability to quantify land‐level change is currently limited by a lack of understanding of the environmental variables controlling the distribution of diatoms, an essential prerequisite for converting variations in fossil diatom assemblages into quantitative estimates of past elevation changes. We present a new modern diatom dataset for the region and explore the implications of the scale of the dataset used in transfer function models on the reconstructions of land‐level change. Modern training sets containing samples from a regional scale are superior to sub‐regional and local‐scale training sets, providing closer estimates for known deformation during the great 1960 Chilean earthquake, a higher proportion of good modern analogues and uncertainty terms up to 42% smaller than previously published reconstructions. Copyright © 2017 The Authors. Journal of Quaternary Science Published by John Wiley & Sons Ltd.